The Relevance of the Virchow Node and Virchow Triad in Renal Cancer Diagnosis - Luiza-Roxana Dorobantu-Lungu; Viviana Dinca; Andrei Gegiu; Dan Spataru; Andreea Toma; Luminita Welt; Mihaela Florentina Badea; Constantin Caruntu; Cristian Scheau; Ilinca Savulescu-Fiedler (Clinics and Practice)
Background: The purpose of this article is to overview the clinical significance of left supraclavicular adenopathy and review the etiology of inferior vena cava (IVC) thrombosis, starting from a presentation of a rare case of renal cell carcinoma (RCCs) with Xp11.2 translocation involving TFE3 gene fusion. This article also aims to review the literature to understand the characteristics of this rare type of renal tumor. Renal cell carcinoma (RCC) associated with Xp11.2 translocation/gene fusion TFE3 is a rare subtype of kidney cancer that was classified in 2016 as belonging to the family of renal carcinomas with MiT gene translocation (microphthalmia-associated transcription factor). The prognosis for these kidney cancers is poorer compared to other types. Methods: We present a case of a 66-year-old man with Virchow–Troisier adenopathy during physical examination, which raises the suspicion of infra-diaphragmatic tumor. The echocardiography highlighted a heterogeneous mass in the right cardiac cavities, and the abdominal ultrasound exam revealed a solid mass at the upper pole of the left kidney. Results: Following computed tomography, magnetic resonance imaging, PET-CT, and histopathological and immunohistochemical examinations, the patient was diagnosed with renal carcinoma with Xp11.2 translocation and TFE3 gene fusion. Conclusions: IVC thrombosis is often associated with neoplastic disease due to the procoagulant state of these patients, the most common malignancies related to IVC thrombosis being represented by RCCs (38%), genitourinary cancers (25%), bronchus and lung cancers, retroperitoneal leiomyosarcoma, and adrenal cortical carcinoma. Imaging methods play a crucial role in differential diagnosis, allowing for the localization of the primary tumor and assessment of its characteristics.